2022
DOI: 10.3390/machines10090721
|View full text |Cite
|
Sign up to set email alerts
|

Granular Resistive Force Theory Extension for Saturated Wet Sand Ground

Abstract: Amphibious environments formed from sand and water present a formidable challenge to the running motion of field robots, as the mixing of granular media (GM) and water makes the force laws of robotic legs more complicated during robot running. To this end, we extended the granular resistive force theory (RFT) to saturated wet granular media, named saturated granular RFT (SGRFT), which can be suitable for saturated wet sand submerged in water. This method can extend RFT for dry GM to saturated wet granular medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In cases where the lift coefficient is negative, the robot will exert more pressure on the ground as the relative velocity of the water flow increases, increasing the likelihood of becoming stuck in sediment. To calculate the lift and drag coefficients, we used the wet particle medium theory for a simplified analysis, as introduced by Ma et al [44]. This theory examines the force dynamics when a moving object infiltrates a wet particle medium, as represented by Equation (10).…”
Section: Inspiration Of Lift and Drag Coefficients On Underwater Atti...mentioning
confidence: 99%
“…In cases where the lift coefficient is negative, the robot will exert more pressure on the ground as the relative velocity of the water flow increases, increasing the likelihood of becoming stuck in sediment. To calculate the lift and drag coefficients, we used the wet particle medium theory for a simplified analysis, as introduced by Ma et al [44]. This theory examines the force dynamics when a moving object infiltrates a wet particle medium, as represented by Equation (10).…”
Section: Inspiration Of Lift and Drag Coefficients On Underwater Atti...mentioning
confidence: 99%
“…We refer to hydrostatic-like pressure as a pressure that increases proportionally with depth ( Aguilar and Goldman, 2016 ). It has been shown that different flowable materials, when stepped upon, generate a reaction force that is almost proportional to the depth of intrusion ( Sharpe et al., 2013 ; Godon et al., 2022 ; Ma et al., 2022 ). In the horizontal direction, thrust can be generated by relying on the cohesion and adhesion of the medium particles with the body.…”
Section: Background On Non-newtonian Yielding Materialsmentioning
confidence: 99%